Relating to voices using compassion focused therapy : a self-help companion - Heriot-Maitland, Charlie; Longden, Eleanor (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Relating to Voices helps people who hear voices to develop a more compassionate understanding and relationship with their voices. In this book, authors Charlie and Eleanor create a warm and caring tone for the reader and a respectful tone for their voices. With the help of regular 'check-in boxes', the book guides the reader towards an understanding of what voices are, what they may represent, and how we can learn to work with them in a way that leads to a more peaceful relationship. It offers a shift away from viewing voices as the enemies, towards viewing them as potential allies in emotional problem-solving. This approach may be different to some others that readers have come across, which can often be about challenging voices, suppressing them, distracting from them, or getting rid of them. The Compassion Focused Therapy (CFT) approach suggests that we can learn to relate to both voices and ourselves in a way that is less about conflict and more about cooperation. This book will be a useful companion for voice-hearers as well as for their supporters and allies in their journey of self-help. It will also be of use to mental health and social service workers"--
Keywords: Emotion-focused therapy; Compassion; Voice; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Psychopathology / Schizophrenia; PSYCHOLOGY / Psychotherapy / General